State subsidies by Uttar Pradesh government: Magnitude, trends and implications - Maurya, Nagendra Kumar; Singh, Ajit Kumar (2016)
The article discusses the magnitude, trends and implications of state subsidies provided by the Government of UP during the period 2002-03 to 2011-12. The discussion covers both explicit and implicit subsidies granted by the State Government. For the purpose of analysis subsidies have been classified into merit and non-merit subsidies. The article adopts cost recovery approach to measure the extent of implicit subsidies. The article shows that the amount of government subsidy both explicit and implicit in UP has been growing rapidly. These subsidies entail a huge economic and fiscal cost. Total subsidies amount to about six per cent of GSDP and about 30 per cent of the revenue expenditure of the State government. The analysis also shows that the subsidies are poorly targeted and suffer from large leakages. It is suggested that all subsidies should be carefully scrutinised at regular intervals to see whether they are serving any useful economic or social purpose. It is also argued that a gradual approach to increase user charges periodically rather than in a single go, after a long time gap would be politically more acceptable. - Reproduced.
Keywords: Subsidies - India - Uttar Pradesh; Subsidies